2008
DOI: 10.1016/j.cct.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiology clinical trial participation in community-based healthcare systems: Obstacles and opportunities

Abstract: Background-The objective of our study was to examine cardiologists' and organizational leaders' interest in clinical trial participation and perceived barriers and facilitators to participation within ten diverse non-profit healthcare delivery systems. Trials play a pivotal role in advancing knowledge about the safety and efficacy of cardiovascular interventions and tests. Although cardiovascular trials successfully enroll patients, recruitment challenges persist. Community-based health systems could be an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…2 ). Our findings are consistent with previous studies that have demonstrated site characteristics such as supportive team environment, clinic engagement, adequate participant population, investigator motivation/engagement, and physician referrals as being critical elements of clinical trial enrollment and overall trial success [ [16] , [17] , [18] , [19] ].…”
Section: Discussionsupporting
confidence: 91%
“…2 ). Our findings are consistent with previous studies that have demonstrated site characteristics such as supportive team environment, clinic engagement, adequate participant population, investigator motivation/engagement, and physician referrals as being critical elements of clinical trial enrollment and overall trial success [ [16] , [17] , [18] , [19] ].…”
Section: Discussionsupporting
confidence: 91%
“…In conducting these trials, the participation of primary healthcare physicians in the community (general practitioners; GPs) and patient recruitment are important issues that need to be properly addressed. Various studies in the literature have reported factors affecting physicians' participation [ 1 , 2 ] and patient recruitment [ 3 , 4 ] in clinical trials, and infrastructure for clinical trials may affect these important issues.…”
Section: Introductionmentioning
confidence: 99%
“…71 – 74 Clinicians were enthusiastic about participation as long as their time demands were not excessive and research staff could complete IRB applications and manage timelines and budgets on their behalf. 71 , 73 Organizational leaders raised concerns about the financial impact of clinical trials, the alignment of trials with their organizational mission, and the impact on member satisfaction of informing members about their eligibility for trials. Health plan members worried that participating in trials might jeopardize their care, although these concerns could be alleviated by a trusted physician.…”
Section: Elements Of Sustainability For Scientific Networkmentioning
confidence: 99%